2021
DOI: 10.1111/cid.12982
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of peri‐implant clinical outcomes of digitally customized and prefabricated abutments: A systematic review and meta‐analysis

Abstract: Background Digitally customized abutments are increasingly used in contemporary implant prosthodontics. Purpose This systematic review and meta‐analysis aimed at comparing the peri‐implant clinical outcomes of digitally customized and prefabricated abutments. Materials and methods The search strategies included electronic databases (PubMed, Embase, Scopus, and Cochrane clinical trials database) and related journals up to September, 2020. A qualitative and quantitative synthesis was performed on data extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
(127 reference statements)
0
8
1
Order By: Relevance
“…However, Schepke et al 7 reported that the CAD/CAM customized abutment showed similar patients' contentment and marginal bone‐level alteration compared with the stock zirconia abutment after 1 year of clinical use. Currently, there are no significant differences between the two abutment fabrication methods in terms of peri‐implant clinical outcomes within the short‐term period according to a recently published meta‐analysis 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Schepke et al 7 reported that the CAD/CAM customized abutment showed similar patients' contentment and marginal bone‐level alteration compared with the stock zirconia abutment after 1 year of clinical use. Currently, there are no significant differences between the two abutment fabrication methods in terms of peri‐implant clinical outcomes within the short‐term period according to a recently published meta‐analysis 8 …”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are no significant differences between the two abutment fabrication methods in terms of peri-implant clinical outcomes within the short-term period according to a recently published meta-analysis. 8 The abutment-implant interface is the region where the occlusal force is transferred to the implant. Therefore, its long-term stability is important for reducing clinical complications and extending the service life of a dental implant.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the role of the customization of implant abutments in aesthetic outcomes should be further elucidated [17]. Numerous systematic reviews and meta-analyses have previously investigated the role of CAD/CAM abutments on pink esthetic score (PES) [6,18,19]. Unfortunately, no clinical data on interproximal soft tissues (e.g., peri-implant papillae) and vestibular soft tissue margin (e.g., midfacial mucosal recession) have been provided.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the number of studies on this topic is limited and mainly focused on the anterior region. 14,15 Clinical studies evaluating monolithic zirconia implant-supported single restorations with CAD/CAM abutments are also scarce. A challenge with monolithic zirconia restorations is the esthetic outcome.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits include a customized emergence profile and a greater distance from the material junction to the peri‐implant bone level compared to stock abutments. Nonetheless, the number of studies on this topic is limited and mainly focused on the anterior region 14,15 . Clinical studies evaluating monolithic zirconia implant‐supported single restorations with CAD/CAM abutments are also scarce.…”
Section: Introductionmentioning
confidence: 99%